Impact of Climate Change on Glacier Melting and Water Security in the Karakoram and Himalayan Region of Pakistan - Hameed, Rahat; Jee, Roshan; Bint E Aslam, Huba; Fatima, Noor (Indus Journal of Bioscience Research, 2025)
The Karakoram and Himalayan area of Pakistan is a vital part of the Earth's cryosphere; it is the principal reservoir of freshwater for millions of people living downstream. This broad review highlights the complex climate-glacier-water nexus of this vulnerable area, and its critical role in Pakistan's water security. The world has observed extensive mass loss of glaciers due to global warming, but the region is heterogeneous across space with strong evidence of stability, referred to as the Karakoram Anomaly; glaciers maintain stability or even gain mass while regional warming progresses. Recent research shows that, despite the anomalous behavior, warming trends are linked with increased temperatures, altered precipitation patterns, and increased deposition of light-absorbing particles, leading to increased melt rates of glaciers in most areas, particularly in the Himalayan ranges. These modifications are more relevant to the Indus River System, as more than 50% of its annual flow comes from melted snow or glaciers. The water insecurity due to reduced flows represents a significant threat to agriculture, hydropower, and social-economic stability for millions living in Pakistan and South Asia. This analysis calls for urgent integrated research approaches and policy frameworks, along with enhanced cooperation across borders, to build climate resilience for all parts of the region.